Identifikasi geological strike dan dimensionalitas berdasarkan analisis phase tensor untuk pemodelan 2D magnetotelurik di lapangan panas bumi “GYF” - Ganap Y. Febrika; Agus Setyawan; Muhammad Irham Nurwidiyanto; Imam B. Raharjo (Youngster Physics Journal, 2017)
Magnetotellurics method is frequently used in exploration of geothermal resources for determining the subsurface resistivity distribution of the Earth. An accurate representation of the Earth’s resistivity structure can be obtained by knowing the direction of geoelectrical strike and dimensionality structure prior to modelling. Besides those both cases, distortion in the data magnetotelluric can lead to errors of interpretation. Therefore, this study was conducted to identify the geoelectrical strike direction and dimensionality structure in the “GYF” geothermal field using phase tensor analysis prior to 2D modelling. Three invariant parameters of phase tensor i.e ellipticity, phase tensor skew angle (β) and Azimuth of phase tensor maximum (α-β) are used to get the information about the dimensionality and geoelectrical strike direction on 65 magnetotelluric data in “GYF” geothermal field. Results of the phase tensor analysis show that the direction of geoelectrical strike is N60°W or 300° at frequency (10-0,2 Hz) and dimensionality of subsurface structure consists of a structure 1D, 2D and 3D. Structure of 1D and 2D is in the frequency range 320 to 0,2 Hz, while the 3D structure is at a low frequency, ie f < 0,2 Hz. Identification of geoelectrical strike and dimensionality in 2D magnetotelluric modelling can minimize misinterpretation.Keywords: Dimensionality, geoelectrical strike, distortion, phase tensor